Seasonal rhythmicity of thermoregulatory physiological responses in fat-rumped sheep under semi-arid tropical environment. Issue 6 (2nd November 2019) - Mohapatra, Arpita; De, Kalyan; Kumar, Davendra; Naqvi, S. M. K.; Singh, Raghvendar
ABSTRACT: The immediate response of animals to fluctuations in environmental temperature is an alteration in their physiological responses. For those who failed to cope, their production performance is affected greatly. Fat-rumped sheep is phenotypically different from the commonly available sheep breeds of the semi-arid tropical environment in India. For assessment of thermoregulatory rhythmicity under extreme seasonal variations of the semi-arid tropical region, six adult fat-rumped (Dumba) rams were selected. The study was carried out in the year 2016–2017. All the rams were maintained under stall-feeding condition with a fixed dietary regime. Respiration rate (RR), pulse rate (PR), skin temperature (ST) and rectal temperature (RT) were recorded at morning (08:00 h), and afternoon (14:00 h) in summer (May–June), winter (December–January) and spring (March–April) for six times in each season at 7 days interval. Body weight was taken at the start and end of each season under study. The meteorological data were recorded twice daily at 8:00 h and 14:00 h for the entire study period. The study indicated significant ( p  < 0.05) variation in RR, PR and ST with respect to season. RT and body weight showed no significant variation among seasons. The result indicated fat-rumped sheep altered their thermoregulatory physiological responses as per the change of season to cope with environmental extremes under semi-arid tropical region.